2019
DOI: 10.1021/acs.est.9b02341
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of Particulate Matter Emissions from a Low-Speed Marine Diesel Engine at Various Loads

Abstract: Particulate matter (PM) emissions from ships are increasingly posing health risks to population living along coastal areas. However, studies on the characteristics of particulate emissions from ships fueled with heavy fuel oil (HFO) are quite rare. In this paper, the characteristics of the PM sampled from the exhaust of a low-speed two-stroke common-rail marine diesel engine fueled with HFO are investigated at different loads. The thermal/optical carbon analyzer was employed to discriminate the elemental and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…High emission factors of marine ships have been reported for particles of 4.8 × 10 15 # kg −1 fuel. 71 The PNSD of marine ship emissions is reported in the range of 25–60 nm, 61,62 which is in line with the PNSD of N′3. Liang et al 72 conducted cruise observations in the South China Sea and found that marine ship emissions accounted for about 44% of PNC 500 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…High emission factors of marine ships have been reported for particles of 4.8 × 10 15 # kg −1 fuel. 71 The PNSD of marine ship emissions is reported in the range of 25–60 nm, 61,62 which is in line with the PNSD of N′3. Liang et al 72 conducted cruise observations in the South China Sea and found that marine ship emissions accounted for about 44% of PNC 500 .…”
Section: Resultssupporting
confidence: 79%
“…In a PMF study for London, fresh and aged traffic has also been distinguished by their differences in the peak time of PNC and mode of PNSD. 23 Inland river navigation close to the DSL site can be an additional possible source of UFPs, 61,62 but there is currently not enough evidence to prove that inland river navigation possesses a morning rush peak like that of vehicular traffic.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…There have been studies already on the parameters of microscopic BC agglomerates and fractal characteristics in diesel engines and combustion flames. In our previous study, the microscopic parameters from a high-power low-speed marine engine were investigated [67].…”
Section: Bc Particles Evolution Morphology and Nanostructurementioning
confidence: 99%
“…Based on the principle of thermophoresis and tempera-ture gradient, a new thermophoresis sampling probe was developed and combined with in situ sampling at different locations of the diesel spray flame. A characteristic analysis of BC has been achieved and presented in our previous publications [67,70]. Figure 11 shows the thermophoretic probing and experimental setup of a constant volume combustion explosive to generate the diesel spray flame used to sample the BC particles.…”
Section: In Situ Sampling and Measurementmentioning
confidence: 99%
“…In 2015, Francesco Di Natale presented a survey on the state-of-the-art knowledge of the physical-chemical properties, toxicology, and emissions of particles from ships [14]. In 2019, Jiang Hao also investigated the characteristics of the CPM sampled from the exhaust of a low-speed two-stroke common-rail marine diesel engine fueled with HFO at different loads [15]. With the optimization of the combustion technology of marine diesel engines, especially after dual-fuel engines have gradually gained market recognition, there are relatively few studies related to their carbon-containing particulate matter emission performance.…”
Section: Introductionmentioning
confidence: 99%